Role of Psychological Capital in Effective Management of Work-stress among Tertiary Institutions’ Staff in Nigeria - Aderibigbe, John K.; Mjoli, Themba Q.; Adebisi, Kolawole S. (Journal of Economics and Behavioral Studies, 2018)
Work-stress is synonymous to occupational stress. It is a common form of strain that is usually experienced by employees, in the course of performing their official duties and responsibilities. In the contemporary world of work, including the Nigerian work environment, work-stress is identified as a ‘corporate epidemic’. Its symptoms are mostly observed physically, psychologically and socially in the lives of affected employees, while the negative effect of occupational stress is specifically, measured on employee performance and organizational effectiveness. It is for the above-described nature and effect of work-stress that this study examined the role of psychological capital in effective management of work-stress among the staff of tertiary institutions in Nigeria. It adopted the explanatory survey research design, purposive and convenience sampling techniques in sampling a total number of 202 (male = 116, 57.4% and female = 86, 42.6%) academic and administrative staff of five (5) public and private tertiary institutions, in the western region of Nigeria, who served as participants in the study. All participants were Nigerians English speakers. Research participation eligibility was strictly based on the current enlistment of employees on the pay-roll of the institutions as at the time of the study. A structured validated questionnaire was used as an instrument. Hypotheses were stated and analyzed based on the data collected. Results revealed that the four psychological capital states jointly influenced work-stress management F(4,197) = 8.375; R2= 0.128; p<.05; resilience (β=0.145; t=1.983; p<.05) and optimism (β=0.294; t=3.756; p<.05) independently influenced workstress management; optimism (r=.224, P(.001)<.01), resilience (r=.350, P(.000)<.01) and hope (r=.247,P(.000)<.01) significantly correlated with work-stress management. The study concluded that psychological capital is one of the important factors that effectively helps in managing work-stress, and suggested that the management of institutions or organizations should sensitize employees on the importance of psychological capital in effective management of work-stress through seminars, trainings and conferences.